SUPPRESSION OF MALE REPRODUCTIVE FUNCTION BY BROWN HT IN RAT - KHATUN, ASHMA; P NATH, PARTHA; MONDAL, MUKTI; PAL, SANGHAMITRA; PAUL, GOUTAM (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Brown HT is an extensively used food color. Our objective was to evaluate the possible toxic effect of Brown HT on male reproductive functions in rats. Methods: Brown HT was administered to male rats orally at 100, 200, and 400 mg/kg body weight/day for a period of 30 days. At the end of this period, different types of parameters related to male reproductive physiology and activities of different antioxidant enzymes were measured by spectrophotometric method using standard protocols. The serum hormonal levels were measured by Chemiluminescence Immuno Assay method using the kit. Results: We have observed significant decrease in mean body weight, gonado somatic index, number of epididymal sperms, percentage of motile sperms, and also decrease in serum level of luteinizing hormone, follicle-stimulating hormone (FSH), and testosterone in a dose dependent manner in Brown HT exposed rats. The activities of antioxidant enzymes such as superoxide dismutase, catalase, glutathione reductase, glutathione peroxidase, and glutathione-S-transferase have been decreased and the level of malondialdehyde, a biomarker of lipid peroxidation has been increased significantly in exposed rats. Histopathology of testes also showed degeneration of germ cells in somniferous tubules in Brown HT exposed rats. Conclusion: According to this result, it is concluded that Brown HT suppresses the male reproductive functions probably by producing oxidative stress in testicular tissues and suppressing the hypothalamus-anterior pituitary-testicular axis in rat.